A Fischer-Tropsch synthesis iron-based catalyst and preparation method thereof
By uniformly distributing Ba elements on the surface of Fischer-Tropsch synthetic iron-based catalysts, a highly dispersed BaCO3 structure is formed, which solves the problem of insufficient thermal stability of the catalyst and achieves a catalytic effect with high activity and low selectivity.
Patent Information
- Application Number
- CN202310462129.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-26
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-04-26
AI Technical Summary
The existing Fischer-Tropsch synthetic iron-based catalysts have problems with insufficient thermal stability in high-temperature reactions, resulting in a decrease in catalyst activity and degradation of performance.
By uniformly distributing a specific amount of Ba elements on the catalyst surface, a highly dispersed BaCO3 structure is formed, and the Fe grain sintering and binding with SiO2 are avoided to form a difficult-to-reduce iron silicate species.
The thermal stability and catalytic activity of the catalyst are significantly improved, the selectivity of CO2 and CH4 is reduced, and the efficiency and product selectivity of Fischer-Tropsch synthesis reaction are improved.
Smart Images

Figure BDA0004201161410000201 
Figure BDA0004201161410000211 
Figure BDA0004201161410000212
Abstract
Description
Technical Field
[0001] The invention relates to the field of Fischer-Tropsch synthesis, and in particular to an iron-based catalyst for Fischer-Tropsch synthesis and a preparation method thereof. Background Art
[0002] The Fischer-Tropsch synthesis reaction can synthesize hydrocarbon compounds with different carbon numbers through CO and H2 under appropriate temperature, pressure and catalyst. The products can be processed to obtain fuels and chemicals. Therefore, the Fischer-Tropsch synthesis can realize the energy conversion of coal, natural gas, biomass, etc. through synthesis gas to oil. The Fischer-Tropsch synthesis technology is divided into high-temperature Fischer-Tropsch synthesis technology and low-temperature Fischer-Tropsch synthesis technology. The reaction temperature of high-temperature Fischer-Tropsch synthesis technology is greater than 300°C, and fluidized bed reactors and molten iron catalysts are usually used. The products are mainly olefins and oxygen-containing compounds; the reaction temperature of low-temperature Fischer-Tropsch synthesis technology is less than 280°C, and fixed bed or slurry bed reactors are usually used. The catalyst uses precipitated iron catalyst (the applicable reaction temperature is 250-280°C) or supported cobalt catalyst (the applicable reaction temperature is 200-230°C), and the products are mainly diesel and wax. Cobalt-based catalysts and iron-based catalysts have different active phase structures and different main and side reaction paths, so they have different formula compositions and preparation methods. Iron-based catalysts with iron as the active component are more suitable for large-scale industrial applications due to their low price, strong resistance to poisoning, and high content of linear α-olefins in the product.
[0003] The iron-based catalyst prepared by precipitation method has small crystals and many active sites, but small crystals are prone to sintering. Fischer-Tropsch synthesis is a highly exothermic reaction, and there are intense exothermic hot spots at the active sites of the catalyst. Therefore, the thermal stability of the catalyst is required to be high. Otherwise, the catalyst is prone to sintering or breaking of the catalyst active particles under the action of the reaction heat, thereby reducing the catalyst performance. Therefore, how to develop an iron-based catalyst with high activity and high thermal stability is an important research and development direction of slurry bed Fischer-Tropsch synthesis technology.
[0004] Commonly used methods for improving catalyst stability are: (1) adding a binder (such as SiO2) to disperse and bond iron grains, (2) improving the preparation process (such as through heat treatment) to improve particle strength and inhibit breakage; (3) adding structural additives (such as Ti, Zr) to improve particle strength. Among them, adding a binder is the most effective method to improve the mechanical strength of the catalyst. At present, almost all Fischer-Tropsch synthesis iron-based catalysts contain SiO2 binder, but although the addition of silicon plays a role in spacing and bonding the active particles of the catalyst to avoid sintering of the active phase of the catalyst, it is a poor thermal conductor, and silicon will also aggregate silicon balls under the action of heat and water vapor, which easily leads to a decrease in catalyst strength. Therefore, it cannot solve the problem of thermal stability of the catalyst well. Some researchers have also improved the mechanical strength of the catalyst by adding structural additives. For example, Chinese patents CN 1245255C, CN 101293206A and CN 101298046A respectively improve the wear resistance of the catalyst by adding zinc, zirconium and titanium additives. However, the above method of inhibiting catalyst breakage by increasing the strength of catalyst particles cannot improve the anti-sintering stability of the catalyst under the action of reaction heat, thereby inhibiting the decrease in catalyst activity caused by sintering of iron grains. Therefore, how to improve the thermal stability of iron-based catalysts in the reaction is still an urgent problem to be solved for Fischer-Tropsch synthesis precipitated iron-based catalysts.
[0005] Chinese patent CN 107684910B discloses a method for preparing an iron-based catalyst for Fischer-Tropsch synthesis, wherein the catalyst components prepared are Fe, Cu, K, Ca and a metal additive, wherein the metal additive is selected from at least one of barium, zinc, lanthanum, magnesium, aluminum, strontium, cerium, lawrencium, platinum, ytterbium, niobium, praseodymium, palladium and cesium. The patent points out that a catalyst with high wear resistance can be obtained by dispersing the precipitation reaction product containing iron, calcium and metal additives in a potassium salt solution in the presence of an organic carboxylic acid, impregnating and spray drying, and roasting, and then mixing the first roasting product with silica sol in the presence of an organic solvent, and then spray drying and roasting for the second time. The catalyst preparation steps proposed in the patent are cumbersome, generally require the addition of multiple additives, and require secondary roasting, and the process cost is relatively high.
[0006] Chinese patent CN 107913714B discloses a Fischer-Tropsch synthesis iron-based catalyst, containing Fe, Cu, Mn, K, SiO2, a first auxiliary agent and a second auxiliary agent, wherein the first auxiliary agent is selected from one or more of Ca, Sr and Ba, and the second auxiliary agent is one or more of La, Ce, Y and Nd. The patent points out that its technical solution provides a catalyst with high stability, low CO2 and CH4 selectivity, and emphasizes that the catalyst in the composition range of the invention can maintain low carbon dioxide selectivity and methane selectivity at a high conversion rate under the synergistic effect of rare earth metals, alkaline earth metals and other auxiliary agents, and effectively inhibit catalyst deactivation; if only rare earth metals or alkaline earth metal auxiliary agents are added separately, the above effects cannot be achieved at the same time. In addition, from the perspective of its preparation method, when the first auxiliary agent solution is added by impregnation, the precipitated catalyst slurry needs to be dried and roasted before impregnation, and the impregnated catalyst needs to be dried and roasted for the second time, and the preparation steps are long and the cost is high. Summary of the invention
[0007] In order to make up for the deficiencies in the prior art, an object of the present invention is to provide an iron-based catalyst for Fischer-Tropsch synthesis, which has excellent catalytic performance and thermal stability, is very suitable for Fischer-Tropsch synthesis reaction, and can significantly improve the reaction efficiency.
[0008] Another object of the present invention is to provide a method for preparing the Fischer-Tropsch synthesis iron-based catalyst.
[0009] A first aspect of the present invention provides an iron-based catalyst for Fischer-Tropsch synthesis, comprising Fe, Cu, K and SiO2, wherein the surface of the iron-based catalyst for Fischer-Tropsch synthesis contains 0.3 to 3% of Ba in terms of molar percentage.
[0010] The Ba element has good heat resistance, stability and thermal conductivity. The present invention uniformly adds a specific amount of Ba element to the Fischer-Tropsch synthesis iron-based catalyst, so that it is highly dispersed on the surface of Fe grains and SiO2 particles and basically does not change the original form of the catalyst. The Ba element dispersed on the surface does not enter the crystal phase of Fe and Si, and can effectively protect the Fe grains in the catalyst, thereby avoiding the sintering of Fe grains and the combination of Fe grains and SiO2 particles to generate difficult-to-reduced iron silicate species, thereby enabling the obtained catalyst to obtain excellent catalytic activity and thermal stability.
[0011] In some preferred embodiments, the surface of the Fischer-Tropsch synthesis iron-based catalyst may contain 0.5 to 2.8% of Ba element by mole percentage. In some more preferred embodiments, the surface of the Fischer-Tropsch synthesis iron-based catalyst may contain 1 to 2.5% of Ba element by mole percentage. In some further preferred embodiments, the surface of the Fischer-Tropsch synthesis iron-based catalyst may contain 1.5 to 2.5% of Ba element by mole percentage.
[0012] In the Fischer-Tropsch synthesis iron-based catalyst provided by the present invention, the Ba element exists in the form of barium carbonate (BaCO3). The Ba element itself has a certain alkalinity, which helps to suppress the generation of methane (CH4) by-products in the Fischer-Tropsch synthesis reaction, improves C5+ product selectivity and olefin selectivity, but also improves CO2 selectivity. The inventors have found that when the Ba element exists in the form of barium carbonate, the role of Ba as an alkaline earth metal additive can be effectively exerted, and the problem of increased CO2 selectivity caused by a strong alkaline additive (such as an alkali metal additive K, Ba in the form of barium hydroxide, etc.) can also be avoided, so that the resulting catalyst can have lower CO2 selectivity and CH4 selectivity at the same time, further improving its catalytic performance.
[0013] In some preferred embodiments, the specific surface area of the Fischer-Tropsch synthesis iron-based catalyst provided by the present invention can be 100 to 250 m 2 In some more preferred embodiments, the specific surface area of the Fischer-Tropsch synthesis iron-based catalyst provided by the present invention can be 120 to 210 m 2 / g.
[0014] In some preferred embodiments, the Fischer-Tropsch synthesis iron-based catalyst provided by the present invention may include the following components by mass ratio: Fe element: Cu element: K element: Ba element: SiO2=100:0.2-5:0.5-8:1-10:10-40. In some more preferred embodiments, the Fischer-Tropsch synthesis iron-based catalyst provided by the present invention may include the following components by mass ratio: Fe element: Cu element: K promoter: Ba element: SiO2=100:2-5:4-8:5-10:20-40.
[0015] The second aspect of the present invention provides a method for preparing the Fischer-Tropsch synthesis iron-based catalyst, the preparation method comprising the following steps:
[0016] S1: forming a mixed aqueous solution of a water-soluble salt of Fe and a water-soluble salt of Cu, preparing a precipitant solution, and adding 0 to 100 wt % of a silicon source to the precipitant solution;
[0017] S2: contacting the mixed aqueous solution with the precipitant solution to perform a precipitation reaction, and separating the obtained precipitation product after the reaction is completed;
[0018] S3: mixing the precipitated product with the K promoter precursor aqueous solution and the remaining silicon source to form a mixed slurry and performing slurry treatment to obtain a catalyst precursor slurry; and
[0019] S4: drying and calcining the catalyst precursor slurry;
[0020] The method of adding the Ba element includes: adding a water-soluble salt of Ba to the mixed aqueous solution of step S1, and making the concentration of Ba lower than 2.0 g Ba / 100 g water; or
[0021] The water-soluble salt of Ba is prepared into an aqueous solution with a concentration lower than 2.0 g Ba / 100 g water, and then added into the mixed slurry of step S3.
[0022] In the preparation method provided by the present invention, by controlling the concentration of Ba element when added, the Ba element can be uniformly distributed on the catalyst surface with a specific content and form very fine particles, and the original catalyst morphology is basically not changed.
[0023] In the preparation method provided by the present invention, the silicon source can be added in whole or in part to the precipitant solution, or in whole or in part to the mixed slurry. For example, the silicon source added to the precipitant solution can be about 0wt%, about 10wt%, about 20wt%, about 30wt%, about 40wt%, about 50wt%, about 60wt%, about 70wt%, about 80wt%, about 90wt%, about 100wt% of the total mass of the silicon source, or any combination of weight ratio intervals, and the remaining silicon source is added to the mixed slurry.
[0024] In the preparation method provided by the present invention, the water-soluble salt of Fe may be a common type in the art, including but not limited to nitrate, hydrochloride or hydrate of Fe, such as Fe(NO3)3·9H2O. In some preferred embodiments, the concentration of Fe in the mixed aqueous solution may be 5 to 100 g / L, for example, about 5 g / L, about 10 g / L, about 20 g / L, about 30 g / L, about 40 g / L, about 50 g / L, about 60 g / L, about 70 g / L, about 80 g / L, about 90 g / L, about 100 g / L or any combination of concentration intervals.
[0025] In the preparation method provided by the present invention, the water-soluble salt of Cu can be any common type in the art, including but not limited to nitrate, hydrochloride or their respective hydrates of Cu, such as Cu(NO3)2·3H2O.
[0026] In the preparation method provided by the present invention, the precipitant may be a common type in the art, including but not limited to one or more of sodium carbonate, ammonia water, ammonium carbonate, sodium hydroxide, potassium hydroxide, and potassium carbonate. In some preferred embodiments, the concentration of the precipitant in the precipitant solution may be 50 to 150 g / L, for example, about 50 g / L, about 60 g / L, about 70 g / L, about 80 g / L, about 90 g / L, about 100 g / L, about 110 g / L, about 120 g / L, about 130 g / L, about 140 g / L, about 150 g / L, or any combination of concentration intervals.
[0027] In the preparation method provided by the present invention, the silicon source can be any common type in the art, including but not limited to one or more of potassium silicate solution, sodium silicate solution, and silica sol solution, wherein the SiO2 concentration can be 10 to 50 wt%. In some preferred embodiments, the SiO2 concentration in the silicon source can be 10 to 30 wt%.
[0028] In the preparation method provided by the present invention, the water-soluble salt of Ba can be one or both of barium nitrate and barium hydroxide.
[0029] In the preparation method provided by the present invention, the K auxiliary agent precursor can be a common type in the art, including but not limited to one or more of potassium nitrate, potassium carbonate, potassium bicarbonate, potassium silicate, and potassium chloride.
[0030] In the preparation method provided by the present invention, in the step S2, the precipitation temperature of the precipitation reaction can be 5 to 95°C (for example, it can be about 5°C, about 20°C, about 40°C, about 60°C, about 80°C, about 95°C, or any combination of temperature intervals), the precipitation time can be 5 to 100 min (for example, it can be about 5 min, about 20 min, about 40 min, about 60 min, about 80 min, about 100 min, or any combination of time intervals), and the pH value during the precipitation process can be controlled at 5 to 10 (for example, it can be about 5, about 6, about 7, about 8, about 9, about 10, or any combination of pH value intervals).
[0031] In the preparation method provided by the present invention, in the step S3, when the mixed slurry is formed, the mixing temperature of each material can be 20-70°C (for example, it can be about 20°C, about 30°C, about 40°C, about 50°C, about 60°C, about 70°C, or any combination of temperature intervals), and the mixing time can be 1-60 min (for example, it can be about 5 min, about 10 min, about 20 min, about 30 min, about 40 min, about 50 min, about 60 min, or any combination of time intervals).
[0032] In the preparation method provided by the present invention, in the step S3, the slurrying temperature of the slurrying treatment can be 10-80°C (for example, it can be about 10°C, about 20°C, about 30°C, about 40°C, about 50°C, about 60°C, about 70°C, about 80°C or any combination of temperature intervals), and the slurrying time can be 10-80min (for example, it can be about 10min, about 20min, about 30min, about 40min, about 50min, about 60min, about 70min, about 80min or any combination of time intervals), and the concentration of the slurry can be controlled to be 10-20wt% during the slurrying treatment.
[0033] In the preparation method provided by the present invention, carbonates present in the preparation system, such as carbonates in the precipitant and / or K additive precursor, help Ba element to form BaCO3. However, when there is no carbonate in the system, or when the carbonate in the system cannot react with the Ba salt to form BaCO3, or when the amount of carbonate is insufficient to convert all Ba elements into BaCO3, it is necessary to introduce CO2 gas additionally after the slurry treatment to ensure the formation of BaCO3. Even if there is carbonate in the system, CO2 gas may be introduced additionally to fully ensure the formation of BaCO3. In some preferred embodiments, the step S3 further includes: introducing CO2 gas for treatment for 0 to 180 minutes after the slurry treatment. In some more preferred embodiments, the step S3 further includes: introducing CO2 gas for treatment for 30 to 180 minutes after the slurry treatment. In other preferred embodiments, the temperature during the CO2 treatment may be the same as the temperature of the slurry treatment.
[0034] In the preparation method provided by the present invention, in step S4, the drying may include the following process: first, the catalyst precursor slurry is spray-dried, and the obtained powder is dried in an air atmosphere at 110-300°C for 1-12 hours. In some preferred embodiments, the hot air inlet temperature of the spray drying may be 180-400°C, and the exhaust air outlet temperature may be 100-220°C.
[0035] In the preparation method provided by the present invention, in the step S4, the calcination temperature can be 400-600° C., and the calcination time can be 1-15 hours. In some preferred embodiments, the catalyst obtained after calcination can be stored in an atmosphere containing CO2 to prevent the catalyst from deteriorating.
[0036] The technical solution provided by the present invention has the following advantages:
[0037] (1) The surface of the Fischer-Tropsch synthesis iron-based catalyst provided by the present invention is uniformly distributed with a specific content of Ba element, which can better exert the thermal stability and thermal conductivity of the Ba element, thereby effectively avoiding Fe sintering and the combination of Fe and SiO2. Therefore, the catalyst has very excellent catalytic activity and thermal stability.
[0038] (2) In the Fischer-Tropsch synthesis iron-based catalyst provided by the present invention, the Ba element exists in the form of barium carbonate, which enables the catalyst to have lower CO2 selectivity and CH4 selectivity when used in the Fischer-Tropsch synthesis reaction.
[0039] (3) The preparation process of the Fischer-Tropsch synthesis iron-based catalyst provided by the present invention is simple, only a small amount of barium salt needs to be added, the conditions are mild and easy to control, no secondary roasting is required, the operability is strong, the cost is low, and it is suitable for large-scale industrial production.
[0040] In summary, the Fischer-Tropsch synthesis iron-based catalyst provided by the present invention is easy to manufacture, has excellent catalytic performance and good heat resistance, and is not easily deactivated after long-term use. Therefore, its application can significantly improve the production efficiency of the Fischer-Tropsch synthesis process and reduce production costs, and has very important economic and social value. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 1 and 2 are XRD spectra of the catalysts prepared in Example 1 and Comparative Example 1, wherein the upper one is the XRD spectrum of the catalyst prepared in Example 1, and the lower one is the XRD spectrum of the catalyst prepared in Comparative Example 1.
[0042] Figure 2 This is the TEM-EDS spectrum of the catalyst prepared in Example 1, wherein the left figure shows the distribution of Ba on the catalyst, and the right figure shows the distribution of Fe. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments.
[0044] The test method used in the present invention is as follows:
[0045] (1) Catalyst composition:
[0046] The components were determined by X-ray fluorescence analyzer (XRF).
[0047] (2) Catalyst specific surface area (BET)
[0048] The static low-temperature nitrogen adsorption method was used to measure the N2 adsorption isotherm at 77K, and then the BET model equation was used to calculate the BET.
[0049] (3) Pore volume (PV)
[0050] The pore volume corresponds to P / P0=0.98~0.99 on the N2 adsorption isotherm measured at 77K.
[0051] (4) Average pore diameter (PD):
[0052] Calculated based on PD=4*PV / BET.
[0053] (5) Ba content on the catalyst surface:
[0054] The results were determined by X-ray photoelectron spectroscopy (XPS).
[0055] Unless otherwise specified, the raw materials or reagents used in the examples and comparative examples of the present invention are commercially available products.
[0056] The percentages used in the embodiments and comparative examples of the present invention are all mass percentages unless otherwise specified.
[0057] Example 1
[0058] Dissolve 10kg Fe(NO3)3·9H2O, 140g Cu(NO3)2·3H2O and 260g Ba(NO3)2 in deionized water to prepare 50 liters of solution, add 5kg ammonium carbonate and 1.84kg silica sol solution with a silica mass concentration of 30% into deionized water to prepare 40 liters of precipitant solution. The mixed solution containing iron, copper and barium is precipitated together with the precipitant solution, the precipitation temperature is 30°C, the precipitation time is 60min, and the pH is controlled at 9.0. After the precipitation reaction is completed, the precipitated slurry is filtered and washed several times to obtain a catalyst precursor filter cake. Dissolve 195g potassium carbonate fully in 1.5kg deionized water to prepare a K additive precursor aqueous solution. Add the K additive precursor aqueous solution to the catalyst precursor filter cake for slurry treatment, control the mass concentration of the slurry to 15%, the slurry temperature to 25°C, and the slurry time to 20min to obtain a catalyst precursor slurry. The inlet temperature was controlled at 380°C and the outlet hot air temperature was controlled at 220°C for spray drying, and the spray drying product was collected. The obtained product was dried at 120°C in an air atmosphere for 12 hours, and then calcined at 450°C in an air atmosphere for 5 hours to obtain a finished catalyst, which was recorded as Catalyst 1.
[0059] Depend on Figure 1 It can be seen that, relative to the catalyst not containing Ba (i.e., the catalyst of Comparative Example 1), the XRD pattern of Catalyst 1 after adding Ba still shows a conventional catalyst peak shape, indicating that the Ba component is highly dispersed in the catalyst and does not form a larger crystal structure, thereby not significantly changing the morphology of the catalyst.
[0060] Depend on Figure 2It can also be seen that the Ba component is highly dispersed in the catalyst and does not form a large crystal structure.
[0061] Example 2
[0062] Dissolve 10kg Fe(NO3)3·9H2O, 140g Cu(NO3)2·3H2O and 26g Ba(NO3)2 in deionized water to prepare 50 liters of solution, add 4kg sodium carbonate and 30g silica sol solution with a silica mass concentration of 20% into deionized water to prepare 40 liters of precipitant solution. Precipitate the mixed solution containing iron, copper and barium together with the precipitant solution, the precipitation temperature is 50°C, the precipitation time is 50min, and the pH is controlled at 8.5. After the precipitation reaction is completed, filter the precipitated slurry and wash it several times to obtain the catalyst precursor filter cake. Dissolve 12g potassium carbonate fully in 1.5kg deionized water to prepare the K additive precursor aqueous solution. The K additive precursor aqueous solution and 660g of silica sol solution with a silica mass concentration of 20% were sequentially added to the catalyst precursor filter cake for slurry treatment, and the mass concentration of the slurry was controlled to be 15%, the slurry temperature was 30°C, and the slurry time was 30min to obtain the catalyst precursor slurry. The inlet temperature was controlled at 350°C and the outlet hot air temperature was controlled at 160°C for spray drying, and the spray drying product was collected. The obtained product was dried at 150°C in an air atmosphere for 10h, and then calcined at 400°C in an air atmosphere for 15h to obtain a finished catalyst, which was recorded as catalyst 2.
[0063] Example 3
[0064] Dissolve 10kg Fe(NO3)3·9H2O and 260g Cu(NO3)2·3H2O in deionized water to prepare 50 liters of solution, add 8kg of 25% ammonia water and 140g of potassium silicate solution with a modulus of 1 and a silica mass concentration of 20% into deionized water to prepare 40 liters of precipitant solution. The mixed solution containing iron and copper is precipitated together with the precipitant solution, the precipitation temperature is 70°C, the precipitation time is 30min, and the pH is controlled at 5.0. After the precipitation reaction is completed, the precipitated slurry is filtered and washed several times to obtain a catalyst precursor filter cake. 104g potassium carbonate and 28g Ba(OH)2 are fully dissolved in 1.5kg deionized water to prepare K additive precursor and Ba additive aqueous solution. 2.63kg of silica sol solution with a silica mass concentration of 20%, Ba additive and K additive precursor aqueous solution were added to the catalyst precursor filter cake in sequence for slurry treatment, and the mass concentration of the slurry was controlled to be 15%, the slurry temperature was 50°C, and the slurry time was 40min. After the slurry was completed, CO2 gas was evenly introduced into the slurry for 120min to obtain a catalyst precursor slurry. The inlet temperature was controlled at 320°C and the outlet hot air temperature was controlled at 140°C for spray drying, and the spray drying product was collected. The obtained product was dried at 180°C in an air atmosphere for 8h, and then calcined at 600°C in an air atmosphere for 6h to obtain a finished catalyst, which was recorded as catalyst 3.
[0065] Example 4
[0066] Dissolve 10kg Fe(NO3)3·9H2O and 10g Cu(NO3)2·3H2O in deionized water to prepare 50 liters of solution, add 12kg of 25% ammonia water to deionized water to prepare 40 liters of precipitant solution. Add the mixed solution containing iron and copper to the precipitant solution for precipitation, control the precipitation temperature to 90°C, the precipitation time to 20min, and the end point pH to 6.0. After the precipitation reaction is completed, filter the precipitate slurry and wash several times to obtain the catalyst precursor filter cake. Add the catalyst precursor filter cake to 1.5 kg of deionized water for slurrying, and fully dissolve 460g of potassium silicate solution with a modulus of 1 and a silica content of 30% in 1.0 kg of deionized water to prepare a silicon additive precursor aqueous solution. Add the silicon additive precursor aqueous solution to the catalyst precursor filter cake slurry, mix thoroughly, add 5wt% nitric acid solution to the slurry, control the end point pH to 7.0, and filter the above slurry to obtain a filter cake. 104g potassium carbonate and 260g Ba(NO3)2 were fully dissolved in 7kg deionized water to prepare aqueous solutions of K and Ba additives, and K and Ba additives were added to the filter cake for slurry treatment. The mass concentration of the slurry was controlled to be 15%, the slurry temperature was 70°C, and the slurry time was 50min. After the slurry was completed, CO2 gas was evenly introduced into the slurry and treated for 150min to obtain a catalyst precursor slurry. The inlet temperature was controlled at 290°C and the outlet hot air temperature was controlled at 120°C for spray drying, and the spray drying product was collected. The obtained product was dried at 200°C in an air atmosphere for 6h, and then calcined at 600°C in an air atmosphere for 8h to obtain a finished catalyst, which was recorded as catalyst 4.
[0067] Example 5
[0068] Dissolve 10kg Fe(NO3)3·9H2O, 260g Cu(NO3)2·3H2O, and 260g Ba(NO3)2 in deionized water to prepare 50 liters of solution, add 3.5kg sodium carbonate and 1.73kg sodium silicate solution with a modulus of 1 and a silica mass concentration of 20% into deionized water to prepare 40 liters of precipitant solution. Add the mixed solution containing iron, copper, and barium to the precipitant solution for precipitation, control the precipitation temperature to 10°C, the precipitation time to 90min, and the endpoint pH to 7.0. After the precipitation reaction is completed, filter the precipitated slurry and wash several times to obtain a catalyst precursor filter cake. Dissolve 12g potassium carbonate fully in 1.5kg deionized water to prepare a K additive precursor aqueous solution. Add the K additive precursor aqueous solution to the catalyst precursor filter cake for slurry treatment, control the mass concentration of the slurry to 15%, the slurry temperature to 10°C, and the slurry time to 60min to obtain a catalyst precursor slurry. The inlet temperature was controlled at 260°C and the outlet hot air temperature was controlled at 110°C for spray drying. The spray drying product was collected and dried at 220°C in an air atmosphere for 4 h. Then, the product was calcined at 550°C in an air atmosphere for 10 h to obtain a finished catalyst, which was recorded as Catalyst 5.
[0069] Example 6
[0070] Dissolve 10kg Fe(NO3)3·9H2O, 10g Cu(NO3)2·3H2O, and 26g Ba(NO3)2 in deionized water to prepare 50 liters of solution, add 4.5kg ammonium carbonate and 120g sodium silicate solution with a modulus of 3.5 and a silica mass concentration of 30% into deionized water to prepare 40 liters of precipitant solution. Add a mixed solution containing iron, copper, and barium to the precipitant solution for precipitation, control the precipitation temperature to 30°C, the precipitation time to 30min, and the endpoint pH to 8.5. After the precipitation reaction is completed, filter the precipitated slurry and wash several times to obtain a catalyst precursor filter cake. Dissolve 195g potassium carbonate in 1.5kg deionized water to prepare a K additive precursor aqueous solution. The K additive precursor aqueous solution and 1.04 kg of silica sol solution with a silica mass concentration of 30% were added to the catalyst precursor filter cake for slurry treatment, and the mass concentration of the slurry was controlled to be 15%, the slurry temperature was 25°C, and the slurry time was 20 minutes to obtain a catalyst precursor slurry. The inlet temperature was controlled at 230°C and the outlet hot air temperature was controlled at 105°C for spray drying, and the spray drying product was collected. The obtained product was dried at 250°C in an air atmosphere for 3 hours, and then calcined at 400°C in an air atmosphere for 12 hours to obtain a finished catalyst, which was recorded as catalyst 6.
[0071] Example 7
[0072] Dissolve 10kg Fe(NO3)3·9H2O and 260g Cu(NO3)2·3H2O in deionized water to prepare 50 liters of solution, add 8kg of 25% ammonia water and 690g of potassium silicate solution with a modulus of 3.5 and a silica mass concentration of 20% into deionized water to prepare 40 liters of precipitant solution. Add the mixed solution containing iron and copper to the precipitant solution for precipitation, control the precipitation temperature to 50°C, the precipitation time to 60min, and the end point pH to 5.0. After the precipitation reaction is completed, filter the precipitated slurry and wash several times to obtain a catalyst precursor filter cake. Fully dissolve 105g Ba(OH)2 in 7kg deionized water to prepare a Ba auxiliary aqueous solution. Fully dissolve 195g potassium carbonate in 1.0kg deionized water to prepare a K auxiliary precursor aqueous solution. The Ba auxiliary agent aqueous solution and the K auxiliary agent precursor aqueous solution were sequentially added to the catalyst precursor filter cake for slurry treatment, and the mass concentration of the slurry was controlled to be 15%, the slurry temperature was 30°C, and the slurry time was 30 minutes. After the slurry was completed, CO2 gas was evenly introduced into the slurry for 180 minutes to obtain a catalyst precursor slurry. The inlet temperature was controlled at 200°C and the outlet hot air temperature was controlled at 105°C for spray drying, and the spray drying product was collected. The obtained product was dried at 280°C in an air atmosphere for 2 hours, and then calcined at 500°C in an air atmosphere for 8 hours to obtain a finished catalyst, which was recorded as catalyst 7.
[0073] Example 8
[0074] Dissolve 10kg Fe(NO3)3·9H2O and 10g Cu(NO3)2·3H2O in deionized water to prepare 50 liters of solution, add 9kg of 25% ammonia water and 2.76kg of sodium silicate solution with a modulus of 1 and a silica mass concentration of 20% into deionized water to prepare 40 liters of precipitant solution. Add the precipitant solution to the mixed solution containing iron and copper for precipitation, control the precipitation temperature to 70°C, the precipitation time to 40min, and the end point pH to 6.0. After the precipitation reaction is completed, filter the precipitated slurry and wash several times to obtain a catalyst precursor filter cake. Fully dissolve 160g Ba(NO3)2 in 7kg deionized water to prepare a Ba auxiliary aqueous solution. Fully dissolve 12g potassium carbonate in 1.0kg deionized water to prepare a K auxiliary precursor aqueous solution. The Ba auxiliary agent aqueous solution and the K auxiliary agent precursor aqueous solution were sequentially added to the catalyst precursor filter cake for slurry treatment, and the mass concentration of the slurry was controlled to be 15%, the slurry temperature was 50°C, and the slurry time was 40 minutes. After the slurry was completed, CO2 gas was evenly introduced into the slurry for 100 minutes to obtain a catalyst precursor slurry. The inlet temperature was controlled at 180°C and the outlet hot air temperature was controlled at 100°C for spray drying, and the spray drying product was collected. The obtained product was dried at 300°C in an air atmosphere for 1 hour, and then calcined at 550°C in an air atmosphere for 8 hours to obtain a finished catalyst, which was recorded as Catalyst 8.
[0075] Example 9
[0076] Dissolve 10kg Fe(NO3)3·9H2O, 140g Cu(NO3)2·3H2O and 160g Ba(NO3)2 in deionized water to prepare 50 liters of solution, add 3kg sodium carbonate and 1.73kg sodium silicate solution with a modulus of 3.5 and a silica mass concentration of 20% into deionized water to prepare 40 liters of precipitant solution. The mixed solution containing iron, copper and barium and the precipitant solution are precipitated together, the precipitation temperature is 30°C, the precipitation time is 80min, and the pH is controlled at 7.0. After the precipitation reaction is completed, the precipitated slurry is filtered and washed several times to obtain a catalyst precursor filter cake. Dissolve 150g potassium nitrate in 1.5kg deionized water to prepare a K additive precursor aqueous solution. Add the K additive precursor aqueous solution to the catalyst precursor filter cake for slurry treatment, control the mass concentration of the slurry to 15%, the slurry temperature to 25°C, and the slurry time to 50min to obtain a catalyst precursor slurry. The inlet temperature was controlled at 380°C and the outlet hot air temperature was controlled at 220°C for spray drying, and the spray drying product was collected. The obtained product was dried at 120°C in an air atmosphere for 12 hours, and then calcined at 600°C in an air atmosphere for 10 hours to obtain a finished catalyst, which was recorded as Catalyst 9.
[0077] Example 10
[0078] Dissolve 10kg Fe(NO3)3·9H2O, 10g Cu(NO3)2·3H2O and 26g Ba(NO3)2 in deionized water to prepare 50 liters of solution, add 4.5kg ammonium carbonate and 460g sodium silicate solution with a modulus of 1 and a silica mass concentration of 30% into deionized water to prepare 40 liters of precipitant solution. Add the precipitant solution to a mixed solution containing iron, copper and barium for precipitation, control the precipitation temperature to 50°C, the precipitation time to 50min, and the endpoint pH to 8.5. After the precipitation reaction is completed, filter the precipitated slurry and wash several times to obtain a catalyst precursor filter cake. Dissolve 20g potassium nitrate in 1.5kg deionized water to prepare a K additive precursor aqueous solution. Add the K additive precursor aqueous solution to the catalyst precursor filter cake for slurry treatment, control the mass concentration of the slurry to 15%, the slurry temperature to 30°C, and the slurry time to 60min to obtain a catalyst precursor slurry. The inlet temperature was controlled at 350°C and the outlet hot air temperature was controlled at 150°C for spray drying. The spray drying product was collected and dried at 150°C in an air atmosphere for 10 hours. Then, the product was calcined at 400°C in an air atmosphere for 9 hours to obtain a finished catalyst, which was recorded as Catalyst 10.
[0079] Embodiment 11
[0080] Dissolve 10kg Fe(NO3)3·9H2O and 260g Cu(NO3)2·3H2O in deionized water to prepare 50 liters of solution, and add 8kg of 25% ammonia water into deionized water to prepare 40 liters of precipitant solution. Add the precipitant solution to the mixed solution containing iron and copper for precipitation, control the precipitation temperature to 90°C, the precipitation time to 20min, and the endpoint pH to 5.0. After the precipitation reaction is completed, filter the precipitated slurry and wash several times to obtain a catalyst precursor filter cake. Dissolve 170g Ba(OH)2 in 7kg deionized water to prepare a Ba auxiliary aqueous solution. Dissolve 290g potassium nitrate in 0.5kg deionized water to prepare a K auxiliary precursor aqueous solution. Ba auxiliary agent aqueous solution, K auxiliary agent precursor aqueous solution and 1.84kg silica sol solution with a silica mass concentration of 30% were added to the catalyst precursor filter cake in sequence for slurry treatment, and the mass concentration of the slurry was controlled to be 15%, the slurry temperature was 70°C, and the slurry time was 20min. After the slurry was completed, CO2 gas was evenly introduced into the slurry for 130min to obtain a catalyst precursor slurry. The inlet temperature was controlled at 320°C and the outlet hot air temperature was controlled at 130°C for spray drying, and the spray drying product was collected. The obtained product was dried at 180°C in an air atmosphere for 8h, and then calcined at 600°C in an air atmosphere for 4h to obtain a finished catalyst, which was recorded as catalyst 11.
[0081] Example 12
[0082] Dissolve 10kg Fe(NO3)3·9H2O and 140g Cu(NO3)2·3H2O in deionized water to prepare 50 liters of solution, add 9kg of 25% ammonia water and 630g of potassium silicate solution with a modulus of 3.5 and a silica mass concentration of 30% into deionized water to prepare 40 liters of precipitant solution. The mixed solution containing iron and copper is precipitated together with the precipitant solution, the precipitation temperature is 90°C, the precipitation time is 20min, and the pH is controlled at 6.0. After the precipitation reaction is completed, the precipitated slurry is filtered and washed several times to obtain a catalyst precursor filter cake. 26g Ba(NO3)2 is fully dissolved in 1.5kg deionized water to prepare a Ba auxiliary aqueous solution. The Ba auxiliary aqueous solution and 530g of potassium silicate solution with a modulus of 3.5 and a silica mass concentration of 30% were sequentially added to the catalyst precursor filter cake for slurry treatment, and the mass concentration of the slurry was controlled to be 15%, the slurry temperature was 70°C, and the slurry time was 30min. After the slurry was completed, CO2 gas was evenly introduced into the slurry for 80min to obtain a catalyst precursor slurry. The inlet temperature was controlled at 290°C and the outlet hot air temperature was controlled at 120°C for spray drying, and the spray drying product was collected. The obtained product was dried at 200°C in an air atmosphere for 6h, and then calcined at 600°C in an air atmosphere for 4h to obtain a finished catalyst, which was recorded as catalyst 12.
[0083] Example 13
[0084] Dissolve 10kg Fe(NO3)3·9H2O, 140g Cu(NO3)2·3H2O and 260g Ba(NO3)2 in deionized water to prepare 50 liters of solution, add 3kg sodium carbonate and 750g silica sol solution with a silica mass concentration of 25% into deionized water to prepare 40 liters of precipitant solution. Add the precipitant solution into a mixed solution containing iron, copper and barium for precipitation, control the precipitation temperature to 70°C, the precipitation time to 30min, and the endpoint pH to 7.0. After the precipitation reaction is completed, filter the precipitated slurry and wash it several times to obtain a catalyst precursor filter cake. Fully dissolve 630g of potassium silicate solution with a modulus of 3.5 and a silica mass concentration of 25% into 1.0kg of deionized water to prepare a K additive precursor aqueous solution. The K additive precursor aqueous solution was added to the catalyst precursor filter cake for slurry treatment, and the mass concentration of the slurry was controlled to be 15%, the slurry temperature was 50°C, and the slurry time was 40 minutes to obtain a catalyst precursor slurry. The inlet temperature was controlled at 260°C and the outlet hot air temperature was controlled at 110°C for spray drying, and the spray drying product was collected. The obtained product was dried at 220°C in an air atmosphere for 4 hours, and then calcined at 450°C in an air atmosphere for 6 hours to obtain a finished catalyst, which was recorded as catalyst 13.
[0085] Embodiment 14
[0086] Dissolve 10kg Fe(NO3)3·9H2O, 30g Cu(NO3)2·3H2O and 130g Ba(NO3)2 in deionized water to prepare 50 liters of solution, and add 4.5kg ammonium carbonate into deionized water to prepare 40 liters of precipitant solution. Precipitate the mixed solution containing iron, copper and barium together with the precipitant solution at a precipitation temperature of 30°C, a precipitation time of 70min, and a pH of 8.5. After the precipitation reaction is completed, filter the precipitated slurry and wash it several times to obtain a catalyst precursor filter cake. Dissolve 580g of potassium silicate solution with a modulus of 3.5 and a silica mass concentration of 25% in 0.5kg of deionized water to prepare a K additive precursor aqueous solution. The K additive precursor aqueous solution and 1.08 kg of silica sol solution with a silica mass concentration of 25% were sequentially added to the catalyst precursor filter cake for slurry treatment, and the mass concentration of the slurry was controlled to be 15%, the slurry temperature was 25°C, and the slurry time was 50 minutes to obtain a catalyst precursor slurry. The inlet temperature was controlled at 230°C and the outlet hot air temperature was controlled at 105°C for spray drying, and the spray drying product was collected. The obtained product was dried at 250°C in an air atmosphere for 3 hours, and then calcined at 550°C in an air atmosphere for 6 hours to obtain a finished catalyst, which was recorded as catalyst 14.
[0087] Embodiment 15
[0088] Dissolve 10kg Fe(NO3)3·9H2O and 70g Cu(NO3)2·3H2O in deionized water to prepare 50 liters of solution, add 8kg of 25% ammonia water and 770g of sodium silicate solution with a modulus of 3.5 and a silica mass concentration of 25% into deionized water to prepare 40 liters of precipitant solution. The mixed solution containing iron and copper is precipitated together with the precipitant solution, the precipitation temperature is 50°C, the precipitation time is 40min, and the pH is controlled at 5.0. After the precipitation reaction is completed, the precipitated slurry is filtered and washed several times to obtain a catalyst precursor filter cake. 85g Ba(OH)2 is fully dissolved in 7kg deionized water to prepare a Ba auxiliary aqueous solution. 110g potassium nitrate is fully dissolved in 0.5kg deionized water to prepare a K auxiliary precursor aqueous solution. The Ba auxiliary agent aqueous solution and the K auxiliary agent precursor aqueous solution were sequentially added to the catalyst precursor filter cake for slurry treatment, and the mass concentration of the slurry was controlled to be 15%, the slurry temperature was 30°C, and the slurry time was 60 minutes. After the slurry was completed, CO2 gas was evenly introduced into the slurry for 100 minutes to obtain a catalyst precursor slurry. The inlet temperature was controlled at 200°C and the outlet hot air temperature was controlled at 100°C for spray drying, and the spray drying product was collected. The obtained product was dried at 280°C in an air atmosphere for 2 hours, and then calcined at 550°C in an air atmosphere for 4 hours to obtain a finished catalyst, which was recorded as catalyst 15.
[0089] Example 16
[0090] Dissolve 10kg Fe(NO3)3·9H2O and 180g Cu(NO3)2·3H2O in deionized water to prepare 50 liters of solution, add 9kg of 25% ammonia water and 550g of sodium silicate solution with a modulus of 3.5 and a silica mass concentration of 25% into deionized water to prepare 40 liters of precipitant solution. The mixed solution containing iron and copper is precipitated together with the precipitant solution, the precipitation temperature is 10°C, the precipitation time is 90min, and the pH is controlled at 6.0. After the precipitation reaction is completed, the precipitated slurry is filtered and washed several times to obtain a catalyst precursor filter cake. 138g Ba(OH)2 is fully dissolved in 7kg deionized water to prepare a Ba auxiliary aqueous solution. 210g potassium nitrate is fully dissolved in 0.5kg deionized water to prepare a K auxiliary precursor aqueous solution. Ba auxiliary agent aqueous solution, K auxiliary agent precursor aqueous solution and 550g silica sol solution with a silica mass concentration of 25% were added to the catalyst precursor filter cake in sequence for slurry treatment, and the mass concentration of the slurry was controlled to be 15%, the slurry temperature was 10°C, and the slurry time was 60min. After the slurry was completed, CO2 gas was evenly introduced into the slurry for 100min to obtain a catalyst precursor slurry. The inlet temperature was controlled at 180°C and the outlet hot air temperature was controlled at 100°C for spray drying, and the spray drying product was collected. The obtained product was dried at 300°C in an air atmosphere for 1h, and then calcined at 600°C in an air atmosphere for 2h to obtain a finished catalyst, which was recorded as catalyst 16.
[0091] Comparative Example 1
[0092] Except for not adding Ba(NO3)2, the remaining steps are the same as those in Example 1 to obtain a finished catalyst, which is recorded as Comparative Agent 1.
[0093] Comparative Example 2
[0094] Except for not adding Ba(NO3)2, the remaining steps are the same as those in Example 2 to obtain a finished catalyst, which is recorded as Comparative Agent 2.
[0095] Comparative Example 3
[0096] Except that Ba(NO3)2 is not added (only 104g potassium carbonate is fully dissolved in 1.0kg deionized water to prepare the K additive precursor aqueous solution) and CO2 treatment is not performed, the remaining steps are the same as Example 3 to obtain a finished catalyst, which is recorded as Comparative Agent 3.
[0097] Comparative Example 4
[0098] Except for using 815 g of Ca(NO3)2·4H2O instead of 260 g of Ba(NO3)2, the remaining steps were the same as those in Example 4 to obtain a finished catalyst, which was recorded as Comparative Agent 4.
[0099] Comparative Example 5
[0100] Except for using 1458 g Mg(NO3)2·6H2O instead of 260 g Ba(NO3)2, the remaining steps are the same as those in Example 5 to obtain a finished catalyst, which is recorded as Comparative Agent 5.
[0101] Comparative Example 6
[0102] Except for using 33.5 g Sr(NO3)2 instead of 26 g Ba(NO3)2, the remaining steps are the same as those in Example 6 to obtain a finished catalyst, which is recorded as Comparative Agent 6.
[0103] Comparative Example 7
[0104] Except for using 300g Ba(NO3)2 to fully dissolve in 7kg deionized water to prepare the Ba auxiliary agent aqueous solution, the remaining steps are the same as Example 7 to obtain a finished catalyst, which is recorded as Comparative Agent 7.
[0105] Comparative Example 8
[0106] Except for using 13g Ba(NO3)2 to fully dissolve in 0.5kg deionized water to prepare the Ba auxiliary agent aqueous solution, the remaining steps are the same as Example 8 to obtain a finished catalyst, which is recorded as Comparative Agent 8.
[0107] Comparative Example 9
[0108] The catalyst was prepared according to the example of Chinese invention patent CN 107684910B, and the catalyst composition was 100Fe:6Cu:5K:2.1Ca:1.9Ba:20SiO2.
[0109] Comparative Example 10
[0110] The catalyst was prepared according to the example of Chinese invention patent CN 107913714B, and the catalyst composition was 100Fe:5.1Cu:2.9K:4.3Nd:1.5Ba:20.7SiO2.
[0111] Comparative Example 11
[0112] Except that CO2 gas is not introduced into the slurry for treatment after slurrying, the remaining steps are the same as those in Example 11 to obtain a finished catalyst, which is recorded as Comparative Agent 11.
[0113] Test Case
[0114] Test equipment: 1L stirred tank.
[0115] Test conditions: 10 g of the catalysts prepared in Examples 1-16 and Comparative Examples 1-11 were mixed with 300 mL of liquid paraffin and placed in a 1 L stirred tank. After reduction activation, the reaction was switched to the Fischer-Tropsch synthesis reaction conditions. The process conditions for reduction activation and Fischer-Tropsch synthesis reaction were as follows:
[0116] (1) Reduction activation: Use syngas with a volume ratio of H2 / CO of 20:1 to reduce by heating (4 h at 30-200 °C, 10 h at 200-265 °C, and 24 h at 265 °C), with a syngas space velocity of 8000 h -1 , the reduction gauge pressure is 3.0MPa.
[0117] (2) Fischer-Tropsch synthesis: After the reduction is completed, the H2 / CO volume ratio of the synthesis gas is adjusted to 3:1 and stabilized for a period of time until the gas phase composition in the reaction tail gas basically does not change with time, which is recorded as the reaction zero point.
[0118] (3) Data calculation: The molar number of CO in the feed was measured and analyzed at the feed port of the stirred tank, and the molar number of CO, CO2, and CH4 in the discharge was measured and analyzed at the discharge port. The CO conversion rate (%), CO2 selectivity (%), and CH4 selectivity (%) were calculated by the following formulas:
[0119] CO conversion rate % = [(CO moles in feed - CO moles in discharge) / CO moles in feed] × 100%;
[0120] CO2 selectivity % = [CO2 mole number in the discharge / (CO mole number in the feed - CO mole number in the discharge)] × 100%;
[0121] CH4 selectivity % = [mole number of CH4 in the output / (mole number of CO in the feed×CO conversion rate % (1-CO2 selectivity %))]×100%.
[0122] The deactivation rate of the catalyst refers to the rate at which the catalyst activity (carbon monoxide conversion rate) decreases from the reaction plateau to the end of the reaction, and the unit is % / h.
[0123] The composition, properties and reaction performance results of the catalysts prepared in Examples 1-16 are shown in Table 1, and the composition, properties and reaction performance results of the catalysts prepared in Comparative Examples 1-11 are shown in Table 2.
[0124] Table 1
[0125]
[0126]
[0127] Table 2
[0128]
[0129] It can be seen from the results of Table 1 and Table 2 that, relative to catalysts to which no Ba element is added (e.g., Comparative Examples 1-3), catalysts to which other types of alkaline earth metal elements are added (e.g., Comparative Examples 4-6), catalysts to which too much or too little Ba element is added (e.g., Comparative Examples 7-8), and existing catalysts to which two metal additives are added (e.g., Comparative Examples 9-10), the Fischer-Tropsch synthesis iron-based catalyst provided by the present invention has a higher CO conversion rate and lower CO2 selectivity and CH4 selectivity, indicating that it has excellent catalytic activity; the Fischer-Tropsch synthesis iron-based catalyst provided by the present invention also has a lower deactivation rate, indicating that it has good thermal stability, which is particularly important for highly exothermic Fischer-Tropsch synthesis reactions under high catalytic activity.
[0130] In addition, it can be seen from Comparative Example 11 that if the Ba element on the catalyst surface is not in the form of barium carbonate, the selectivity of CO2 will be significantly increased and the stability of the catalyst will be significantly reduced.
[0131] Unless otherwise defined, the terms used in the present invention have the meanings commonly understood by those skilled in the art.
[0132] The embodiments described in the present invention are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Those skilled in the art may make various other substitutions, changes and improvements within the scope of the present invention. Therefore, the present invention is not limited to the above embodiments, but is only limited by the claims.
Claims
1. A Fischer-Tropsch synthesis iron-based catalyst comprising Fe, Cu, K and SiO2, characterized in that: The surface of the Fischer-Tropsch synthesis iron-based catalyst contains 0.3-3% of Ba element in terms of molar percentage. The Ba element on the surface of the Fischer-Tropsch synthesis iron-based catalyst exists in the form of barium carbonate, and the mass ratio of Fe element:Cu element:K element:Ba element:SiO2 is 100:0.2-5:0.5-8:1-10:10-40.
2. The Fischer-Tropsch synthesis iron-based catalyst according to claim 1, characterized in that The specific surface area of the Fischer-Tropsch synthesis iron-based catalyst is 100 to 250 m 2 / g.
3. The method for preparing the Fischer-Tropsch synthesis iron-based catalyst according to claim 1 or 2, characterized in that: The following steps are involved: S1: forming a mixed aqueous solution of a water-soluble salt of Fe and a water-soluble salt of Cu, preparing a precipitant solution, and adding 0 to 100 wt % of a silicon source to the precipitant solution; S2: contacting the mixed aqueous solution with the precipitant solution to perform a precipitation reaction, and separating the obtained precipitation product after the reaction is completed; S3: mixing the precipitated product with the K additive precursor aqueous solution and the remaining silicon source to form a mixed slurry and performing slurry treatment, and after the slurry treatment, introducing CO2 gas for 0 to 180 minutes to obtain a catalyst precursor slurry; as well as S4: drying and calcining the catalyst precursor slurry; The method of adding the Ba element includes: adding a water-soluble salt of Ba to the mixed aqueous solution of step S1, and making the concentration of Ba lower than 2.0g Ba / 100g water; or The water-soluble salt of Ba is prepared into an aqueous solution with a concentration lower than 2.0 g Ba / 100 g water, and then added into the mixed slurry of step S3.
4. The preparation method according to claim 3, characterized in that: The water-soluble salt of Fe is nitrate, hydrochloride or hydrate of Fe, and the water-soluble salt of Cu is nitrate, hydrochloride or hydrate of Cu; and / or The precipitant is selected from one or more of sodium carbonate, ammonia water, ammonium carbonate, sodium hydroxide, potassium hydroxide and potassium carbonate.
5. The preparation method according to claim 4, characterized in that: In the mixed aqueous solution, the concentration of Fe is 5 to 100 g / L.
6. The preparation method according to claim 4, characterized in that: The concentration of the precipitant is 50-150 g / L.
7. The preparation method according to claim 3, characterized in that: The silicon source is selected from one or more of potassium silicate solution, sodium silicate solution and silica sol solution, wherein the SiO2 concentration is 10-50wt%; and / or The water-soluble salt of Ba is one or both of barium nitrate and barium hydroxide; and / or The K additive precursor is one or more of potassium nitrate, potassium carbonate, potassium bicarbonate, potassium silicate and potassium chloride.
8. The preparation method according to claim 3, characterized in that: In step S2, the precipitation temperature of the precipitation reaction is 5 to 95° C., the precipitation time is 5 to 100 min, and the pH value during the precipitation process is controlled at 5 to 10; and / or In the step S3, the slurrying temperature of the slurrying treatment is 10-80° C., the slurrying time is 10-80 min, and the concentration of the slurry is controlled to be 10-20 wt % during the slurrying treatment.
9. The preparation method according to claim 3, characterized in that: After the slurrying treatment is completed, CO2 gas is introduced for treatment for 30 to 180 minutes.
10. The preparation method according to claim 3, characterized in that: In the step S4, the drying includes the following process: firstly, the catalyst precursor slurry is spray-dried, and the obtained powder is dried in an air atmosphere at 110-300° C. for 1-12 hours.
11. The preparation method according to claim 10, characterized in that: The hot air inlet temperature of the spray drying is 180-400°C, and the exhaust air outlet temperature is 100-220°C.
12. The preparation method according to any one of claims 3 to 11, characterized in that: In the step S4, the calcination temperature is 400-600° C. and the calcination time is 1-15 hours.
Citation Information
Patent Citations
Iron base catalyst for fischer-tropsch synthesis and preparation method thereof
CN101293206A
Iron catalyst containing titanium deposition for catalyzing Fischer-Tropsch synthesis reaction and method for producing the same
CN101298046A
A Fischer-Tropsch synthesis iron-based catalyst and its preparation method
CN107684910B
Iron-based catalysts for Fischer-Tropsch synthesis, their preparation methods, and Fischer-Tropsch synthesis methods
CN107913714B
Iron base catalyzer through Fischer-Tropsch synthesis and preparation method
CN1245255C
Cited By
A modified Fe2O3-Al2O3 composite oxide, its preparation, and its application in Fischer-Tropsch synthesis.
CN122828738A